Forefoot reconstruction in brachymetatarsia - I. V. Usoltsev; S. N. Leonova; M. A. Kosareva (Acta Biomedica Scientifica, 2023)
Background. Brachymetatarsia is a rare disease characterized by abnormal shortening of one or more metatarsal bones. The clinical picture is most often dominated by complaints of aesthetic dissatisfaction, as well as pain in the forefoot caused by mechanical dysfunction. A radical way to solve the problem is surgical treatment. The aim. To demonstrate a rare clinical observation of a patient with bilateral brachymetatarsia of both feet. Materials and methods. The article presents a case of stepwise treatment of a patient with bilateral brachymetatarsia with shortening of the III and IV metatarsal bones in combination with hallux valgus. Results and discussion. According to the protocol, the patient underwent stepwise reconstruction of the forefoot of both feet with intervention on all five metatarsal bones. After all the rehabilitation measures, there was a complete restoration of all functions of both lower limbs after the surgery, and the patient was satisfied with the aesthetic result of the surgical treatment. Conclusions. The obtained result of treatment of a patient with bilateral brachymetatarsia allows us to conclude that the use of this group of techniques is acceptable with the obligatory preoperative calculation of the necessary shortening and lengthening of the metatarsal bones, focusing on the parameters of the metatarsal formula of the forefoot, even in combination with other deformities.